Individual Land Tenure and the Challenges of Sustainable Land Use and Management in a Semi-arid Region of China - Zhao, Yongjun (Sustainability in Debate, 2010)
China’s farmland tenure, characterised by a household responsibility system (HRS) and collective landownership, has contributed to the continuation of poverty and natural resource deterioration in semiarid regions. Incongruent with local ecological, social and political conditions, the HRS has been linked to rising social and political tensions. Drawing on ethnographic research in Guyuan County, North China, this paper provides peasants’ experiences of and views on the land issue and examines the linkages between land tenure, poverty and the governance of natural resources””grassland, forest land, farmland and water. It shows that an appropriate land tenure system can only be achieved if the fragmentation and individualization of the HRS are reformed through an innovative institutional design. The paper also contributes to a critical understanding of China’s agrarian reform by articulating the need for land tenure diversity serving the overall goal of sustainable land use and management and shaping sound statepeasant relations.